Towards a new framework for TPM compliance testing - Elhagari, Usama Tharwat (2014)
Trusted Computing Group (TCG) has proposed the Trusted Computing (TC) concept. Subsequently, TC becomes a common base for many new computing platforms, called Trusted Platform (TP) architecture (hardware and software) that, practically, has a built-in trusted hardware component mounted at the hardware layer and a corresponding trusted software component installed at the operating system level. The trusted hardware component is called Trusted Platform Module (TPM) whose specification has been issued by TCG group and it is implemented by the industry as a tamper- resistant integrated circuit. In practice, the security of an IT TPM-enabled system relies on the correctness of its mounted TPM. Thus, TPM testing is urgently needed to assist in building confidence of the users on the security functionality provided by the TPM. This paper presents the state of the art of the modelling methods being used in the TPM compliance testing. Finally, the paper proposes new framework criteria for TPM Testing that aim at increasing the quality of TPM testing.